2003
DOI: 10.1108/00215080380001149
|View full text |Cite
|
Sign up to set email alerts
|

Explaining county‐level variability in farm service agency farm loan programs

Abstract: in farm credit markets: identifying market segments served by the farm credit system and commercial banks", Agricultural Finance Review, Vol. 64 Iss 2 pp. 167-186 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Meanwhile, small community banks, defined as those having less than $250 million in total assets, comprised over half of all new FSA bank guaranteed loan volume. While overall market share for FSA guarantees in recent years has ranged between 4 and 5 percent, FSA guarantees tend to be much more important in certain regions and among certain groups (Dodson and Koenig, 2003). Specifically, usage of FSA-guaranteed programs has tended to be greater among young and beginning farmers and in more economically depressed regions.…”
Section: Commercial Banks and Fsa-guaranteed Loan Programsmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, small community banks, defined as those having less than $250 million in total assets, comprised over half of all new FSA bank guaranteed loan volume. While overall market share for FSA guarantees in recent years has ranged between 4 and 5 percent, FSA guarantees tend to be much more important in certain regions and among certain groups (Dodson and Koenig, 2003). Specifically, usage of FSA-guaranteed programs has tended to be greater among young and beginning farmers and in more economically depressed regions.…”
Section: Commercial Banks and Fsa-guaranteed Loan Programsmentioning
confidence: 98%
“…In a subsequent analysis, Settlage et al (2006) found banks with greater experience originating FSA-guaranteed loans had higher probabilities of originating guaranteed loans in the future. Dodson and Koenig (2003) used county-level data to model the use of FSA farm loan programs between 1995 and 1999. Escalante et al (2006) found that the debt-repayment margin ratio and current ratio influenced loan approval for FSA direct and guaranteed loans.…”
Section: Commercial Banks and Fsa-guaranteed Loan Programsmentioning
confidence: 99%
“…The borrower region was defined as the ten USDA Farm Production regions (US Department of Agriculture, Economic Research Service, 2010). Distinct regional differences in FSA loan programs, as shown in previous studies, would suggest regional differences in loan duration (Dodson and Koenig, 2003;Ahrendsen et al, 2011).…”
Section: Model Specificationmentioning
confidence: 52%
“…The difference in cost makes clear the high per loan subsidy of the IA program and why IA loans are so attractive to borrowers and their lenders. Dodson and Koenig (2003) seek to explain the disparity across US counties in utilizing FSA farm loan programs. They use a Tobit regression model to test for the relationship between observed use-patterns of FSA loan programs and related factors.…”
Section: Related Studiesmentioning
confidence: 99%
“…The variable equals one if at least one IA loan was made in the county over the five years. Dodson and Koenig (2003) hypothesize that the use of the IA program within a county would increase guaranteed loan use. The IA binary variable has a positive and significant effect on the share of farmers obtaining FSA loan guarantees, as expected.…”
Section: Related Studiesmentioning
confidence: 99%